2022
DOI: 10.1177/02655322221076153
|View full text |Cite
|
Sign up to set email alerts
|

Local placement test retrofit and building language assessment literacy with teacher stakeholders: A case study from Colombia

Abstract: This article provides a single, common-case study of a test retrofit project at one Colombian university. It reports on how the test retrofit project was carried out and describes the different areas of language assessment literacy the project afforded local teacher stakeholders. This project was successful in that it modified the test constructs and item types, while drawing stronger connections between the curriculum and the placement instrument. It also established a conceptual framework for the test and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The design and administration of these types of testing is also another source for analysis, by showing the gap between testing literacy and training resulting in mismatches, unfair and irregular practices, and test designs as well as in a misguide for the decisions stakeholders must take (Ramírez, 2020). In a similar vein, initiatives designed to assist educators in comprehending, formulating, and implementing standardized tests present numerous avenues for local stakeholders to enhance and demonstrate their proficiency in language assessment (Janssen, 2022). Finally, reflections made on the perceived need for standardized testing emphasizes its importance as a reliable and valid assessment tool to measure language knowledge; nevertheless, the argument can be made that in order to make it more accessible to a greater number of teachers, a migration to the online world should be made.…”
Section: Standardized Testingmentioning
confidence: 99%
“…The design and administration of these types of testing is also another source for analysis, by showing the gap between testing literacy and training resulting in mismatches, unfair and irregular practices, and test designs as well as in a misguide for the decisions stakeholders must take (Ramírez, 2020). In a similar vein, initiatives designed to assist educators in comprehending, formulating, and implementing standardized tests present numerous avenues for local stakeholders to enhance and demonstrate their proficiency in language assessment (Janssen, 2022). Finally, reflections made on the perceived need for standardized testing emphasizes its importance as a reliable and valid assessment tool to measure language knowledge; nevertheless, the argument can be made that in order to make it more accessible to a greater number of teachers, a migration to the online world should be made.…”
Section: Standardized Testingmentioning
confidence: 99%
“…Empirical studies on teachers' LAL have indicated that teachers expect to learn about language assessment through practical, hands-on tasks in which theory is presented and used (Fulcher, 2012;Giraldo & Murcia, 2018;Tsagari, 2021). Courses deriving from this teacherbased feedback have, accordingly, focused on engaging teachers in learning about assessment through a praxis-based approach (Arias et al, 2012;Baker & Riches, 2017;Janssen, 2022; The existing literature on LAL courses primarily report their outcomes, rather than the participants' perceptions towards how they learned or were taught. Of course, the purpose of most existing reports was not to evaluate participants' perceptions of their learning.…”
Section: Lal Coursesmentioning
confidence: 99%